Transformative Insights into Corrosion Inhibition: A Machine Learning Journey from Prediction to Web-Based Application - Dzaki Asari Surya Putra; Nicholaus Verdhy Putranto; Nibras Bahy Ardyansyah; Gustina Alfa Trisnapradika; Muhamad Akrom (Jurnal Ilmu Komputer dan Informasi, 2025)
This study focuses on the exploration and evaluation of machine learning (ML) models to analyze expired pharmaceutical data for their potential use as corrosion inhibitors. Additionally, the entire modeling process is integrated into a user-friendly platform through a Streamlit service-assisted corrosion inhibitor website, facilitating broader accessibility and practical application. The models are trained offline to ensure accurate performance, eliminating the need for users to retrain the models themselves. This approach simplifies the user experience by offering a ready-to-use prediction service directly on the website platform. Among the various ML models implemented, XGB demonstrated the highest performance with an R2-score of 0.99999999. Given that many chemists are not familiar with informatics coding, the researchers developed a Streamlit-based website that includes tools to customize the models. The end product of this work is a corrosion inhibitor experimentation tool that eliminates the need for users to code, making advanced ML techniques accessible to a broader audience within the chemistry community.